FERTILITY AND FERTILE PERIOD OF DUCK EGGS AFTER ARTIFICIAL INSEMINATION WITH MUSCOVY DUCK SEMEN SUPPLEMENTED WITH VITAMIN C AND E - Hidayat, Nu'man -; Ismoyowati, Ismoyowati -; Hidayah, Chomsiatun Nurul; Nugroho, Aras Prasetiyo (Universitas Syiah Kuala, 2019)
The aim of this research was to investigate the influence of duck variants and addition of vitamins into muscovy duck semen on fertility and fertile period of duck eggs after artificial insemination. Semen was collected from five muscovy ducks and divided into 3 treatment groups: without vitamin supplementation (A0), supplementation of 400 g/mL vitamin C (A1), and supplementation of 80 g/ml vitamin E (A2). Each semen was inseminated into female ducks of Magelang (B1) and Mojosari (B2) variants. Complete Random Design was used with 3x2 factorial. The results showed that vitamins and duck variants had no significant interaction (P0.05) with fertility and fertile period. The duck variant had no effect (P0.05) on fertility and fertile period, while the addition of vitamins significantly affected (P0.01) the fertility and fertile period. The addition of 400 g/mL vitamin C increased fertility by 22.280.20% but reduced the fertile period by 7.83.5 days, whereas 80 g/mL of vitamin E increased fertility by 11.572.47% but reduced fertile period by 12.30.9 days. It can be concluded that the addition of 400 g/mL of vitamin C and 80 g/mL of vitamin E in Muscovy duck semen increased fertility but shortened fertile period of duck eggs after artificial insemination.